PENGARUH PARTISIPASI KARYAWAN PADA PELATIHAN PLN CORPORATE UNIVERSITY TERHADAP KOMPETENSI DAN KINERJA KARYAWAN - Rizky Caesariza Saddam Hussein; Laila Refiana Said; Rini Rahmawati (Universitas Lambung Mangkurat, 2016)
This research aims to analyze the influence of employees participation in the training of PLN Corporate University (X) as the exogenous variable toward competence (Y1) and employees performance (Y2) as the endogenous variable at PLN Corporate University Udiklat Banjarbaru. The method of this research used descriptive quantitative research by distributing questionnaires to 120 employees who have followed the training. The samples were chosen by using accidental sampling. The variable measurement technique used Likert scale with weight scale from 1 to 5. In order to find out the effects of variable X to variable Y1 and Y2, Structural Equation Modelling (SEM) was used as an analytical technique. The result of research concluded that (1) there was a positive and significant influence of the exogenous variable (X) on the endogenous variables (Y1 and Y2); (2) PLN employees participation in Corporate University training (X) influences the competences of employees (Y1) by 43,6%, which has a direct influence on the performance of employees by 33% and has the indirct effects by 15,7%; (3) the competence variable (Y1) influences the employees performance by 36,1%.